International Perspectives on School Settings, Education Policy and Digital Strategies A Transatlantic Discourse in Education Research - Jornitz, Sieglinde; Wilmers, Annika (Verlag Barbara Budrich, 2021)
An exchange on education ideas has shaped the transatlantic discourse in education for a long time. Over the past two decades education science has increasingly become networked internationally. Since 2015, the Office for International Cooperation in Education at DIPF | Leibniz Institute for Research and Information in Education has organized international sessions on education research at the Annual Meetings of the American Educational Research Association, thus providing a floor for transatlantic exchange on current research topics. The volume gives an overview of the transatlantic activities in education research with regard to these sessions representing a collection of topics ranging from school development over the use of large scale assessment and digital data in education to questions related to migration and public education or the economization of education. At the same time the volume offers a reflection on the assets and obstacles of international exchange.